An optical and thermal analysis of translucent concrete considering its dynamic transmittance. (1st September 2022) - Su, Xiaosong; Zhang, Ling; Liu, Zhongbing; Luo, Yongqiang; Liang, Ping; Lian, Jinbu
Abstract: Translucent concrete (TC) is promising to transmit daylight into buildings with high thermal performance and energy-saving potential. However, most of the existing studies on TC omit its dynamic transmittance. More research is required to analyze the impact of dynamic transmittance on the optical and thermal performance of TC walls, and to investigate how to take advantage of this distinctive feature so that the building energy-saving potential of TC walls can be fully exploited. In this study, an optical and thermal model of TC embedded with optical fibers (OFs) was developed considering the dynamic transmittance of TC under the influence of solar incidence angle. The model was validated with experimental data. By using the model, the effects of numerical aperture (NA), fiber volumetric ratio (FVR) and solar incident angle on TC were revealed. In addition, a kind of novel TC with inclined OFs was proposed to achieve improved climate-responsive transmittance, which can reduce the dependence on high NA OFs. It was found that in Changsha the direct radiation transmittance of an OF (NA = 0.51, tilt angle = 60°) embedded in TC walls can be controlled within 0.20 in summer, while it can increase up to 0.90 in winter. Though the inclusion of OFs imposes an adverse effect on the wall insulation, TC walls can reduce daily heat loss by about 9.14% and increase daily heat gain by about 51.66% in winter, contributing to energy conservation in buildings.